Sakralitas Digital Hindu Bali Translokasi Ruang Suci ke Media Sosial - Putra, Anggara Putu Dharma (Jayapangus Press, 2026)
Digital transformation has blurred the boundaries between the sacred and the profane, positioning social media not merely as a means of communication but also as a new arena for religious expression. In the context of Balinese Hinduism, the translocation of sacred spaces onto digital timelines raises questions about how sacredness is produced, perceived, and renegotiated within the digital ecology. This study aims to examine the phenomenon of uploaded sacredness by emphasizing the dynamics of visual representation, authority, and online community validation. This research employs a qualitative approach through digital ethnography and visual anthropology. Data were collected through online observation, documentation of 120 posts on Instagram, Facebook, TikTok, and YouTube (2022–2024), as well as semi-structured interviews with 20 key informants, including priests, content creators, and Hindu practitioners. Data analysis was conducted inductively through visual coding, digital discourse analysis, and ethnographic interpretation. The study reveals four main findings. First, sacred spaces are aesthetically represented through photos, videos, and poetic captions that extend religious experiences into the virtual sphere. Second, the emergence of hybrid rituals marks the convergence of offline ritual practices and online content production. Third, religious authority shifts into the digital realm, producing dynamics of post-traditional religiosity in which young priests and content creators become authoritative figures. Fourth, community validation through likes, comments, and reshares constitutes the legitimacy of digital sacredness, although often accompanied by tensions between sanctity and commodification. The study demonstrates that sacredness does not disappear in its translocation to social media but is re-mediated through visual aesthetics, community participation, and platform logics. This research contributes to the study of religion, visual culture, and digital anthropology by asserting that uploaded sacredness is a hybrid religious phenomenon that is both global and local, while also enriching theoretical frameworks on religious mediation in the era of digital disruption.